General practitioners' retirement plans and what influences them. Issue 6531 (17th May 1986) - Wakeford, R; Roden, M; Rothman, A
Abstract : The results of a study of the attitudes of 197 general practitioners aged 55 and over towards retirement and their plans for retirement are reported. Few wished to retire very early, and only a further 40% definitely planned a clean break from practice. Nearly half planned on taking "24 hour retirement, " even though most (78%) will be entitled to full pension rights. Job satisfaction and health were the most important factors influencing the timing of the retirement. Seventy seven per cent thought that there should be no formal retirement policy, 79% wanted no compulsory retirement age, and 80% wanted no further controls or safeguards directed at older practising general practitioners. Half of the general practitioners in the sample were not looking forward to retirement. Personal discussions with respondents aged 65 and over suggested that there are many older general practitioners who plan to practise for some time, who feel that they will know when the time has come to stop, but who often express the hope that they may "die in harness." A large proportion of older doctors are in single-handed practice. In view of this, and also of the evidence from North America which suggests that older doctors may practise inferior medicine, it is thought that the ability of such general practitioners to evaluate their competence should be studied by methods such as peer assessment techniques.